Maize Tolerance to Salinity of Irrigation Water - Wanti Mindari; . Maroeto; . Syekhfani (UNIVERSITY OF LAMPUNG, 2011)
Crop salt tolerance is generally assessed as the relative yield response to the increasing of root zone salinity. This paper studied the maize tolerance under salinine water (ECw) and their relationship with the changes of soil chemistry characteristics, crop growth and yield of maize. The seven level of water salinity were 0.66, 0.93, 1.57, 1.68, 2.46, 3.35, 3.85 mS cm-1 and three local maize from Madura, Pasuruan and Probolinggo were evaluated to soil electric conductivity (ECe), pH, available -N. -P. and -K as well as plant height and seed weight The experiment indicated that saline water (ECw) up to a certain concentration increased soil salinity (ECe) and pH, but decreased nutrient availability, plant height, fresh and dry weight of maizes. ECw level between 1.5 to 1.7 mS cm-1 gave the best results compared to others, because of soil nutrients and water availability optimum. Maize of Madura and Pasuruan were more tolerant than Probolinggo giving ECw up to 3. 85 mS cm-1, although their maize seed dry weight were lower.